Escalating and sustained immunovirological dissociation among antiretroviral drug-experienced perinatally human immunodeficiency virus-1-infected children and adolescents living in the Central African Republic: A STROBE-compliant study. Issue 21 (22nd May 2020) - Mossoro-Kpinde, Christian Diamant; Gody, Jean-Chrysostome; Mboumba Bouassa, Ralph-Sydney; Moussa, Sandrine; Jenabian, Mohammad-Ali; Péré, Hélène; Charpentier, Charlotte; Matta, Mathieu; Longo, Jean De Dieu; Grésenguet, Gérard; Djoba Siawaya, Joël Fleury; Bélec, Laurent
Abstract : Abstract: Sub-Saharan Africa has the vast majority (∼90%) of new pediatric acquired immunodeficiency syndrome cases worldwide. Biologically monitoring HIV-infected pediatric populations remains challenging. The differential interest of human immunodeficiency virus (HIV)-1 RNA loads and CD4 T-cell counts is debated for the treatment of pediatric acquired immunodeficiency syndrome patients. Long-term antiretroviral treatment (ART) outcomes regarding immunological and virological surrogate markers were longitudinally evaluated between 2009 and 2014 (over 57 months) in 245 perinatally HIV-1-infected children and adolescents born from HIV-infected mothers, treated at inclusion for at least 6 months by the World Health Organization-recommended ART in Bangui, Central African Republic. Patients were monitored over time biologically for CD4 T-cell counts, HIV-1 RNA loads, and drug resistance mutation genotyping. Children lost to follow-up totaled 6%. Four categories of immunovirological responses to ART were observed. At baseline, therapeutic success with sustained immunological and virological responses was observed in 80 (32.6%) children; immunological and virologic nonresponses occurred in 32 (13.0%) children; finally, the majority (133; 54.2%) of the remaining children showed discordant immunovirological responses. Among them, 33 (13.4%) children showed rapid virological responses to ART with an undetectable viral load, whereas immunological responses remained absent after 6 months of treatment and increased progressively over time in most of the cases, suggesting slow immunorestoration. Notably, nearly half of the children (40.8% at baseline and 48.2% at follow-up) harbored discordant immunovirological responses with a paradoxically high CD4 T-cell count and HIV-1 RNA load, which are always associated with high levels of drug resistance mutations. The latter category showed a significant increase over time, with a growth rate of 1.23% per year of follow-up. Our STROBE-compliant study demonstrates the high heterogeneity of biological responses under ART in children with frequent passage from 1 category to another over time. Close biological evaluation with access to routine plasma HIV-1 RNA load monitoring is crucial for adapting the complex outcomes of ART in HIV-infected children born from infected mothers.